The usual suspect: cross-sectional study of fundal pressure at second stage of delivery and the association with pelvic floor damage - TAKMAZ, TAHA; TAKMAZ, TAHA; AYDIN, SERDAR; AYDIN, SERDAR; Gorchiyeva, Irana; GÖKMEN KARASU, AYŞE FİLİZ; GÖKMEN KARASU, AYŞE FİLİZ (My University, 2020)
Introduction and hypothesis Uterine fundal pressure is applied to accelerate birth by increasing the expulsive force of the uterus in the second stage of delivery. The aim of the study was to evaluate the effect of using uterine fundal pressure during the second stage of delivery on the rate of pelvic floor damage among primiparous women using three-dimensional transperineal ultrasonography. Methods The women were divided into two groups: the fundal pressure group included women where the fundal pressure maneuver was applied (n = 39); the control group included women who delivered spontaneously without fundal pressure (n = 47). 3D-TPU was performed within 48 h of delivery, and LAM biometry, LAM defect and loss of tenting were determined. Results Anteroposterior hiatal dimensions on resting, maximal Valsalva and maximal PFMC were found to be higher in the fundal pressure group (p < 0.0001,p = 0.008,p = 0.007, respectively). The mean hiatal area at rest was larger in the fundal pressure group than in the control group (p = 0.04). The rate of LAM defect was significantly higher in the fundal pressure group (p = 0.001). The rate of loss of tenting was significantly higher in the fundal pressure group (p < 0.0001). According to multivariate regression models, the fundal pressure was the only independent factor associated with LAM defect (OR = 5.63; 95% CI = 12.01-15.74) and loss of tenting (OR = 8.74; 95% CI = 2.89-26.43). Conclusions Fundal pressure during the second stage of delivery is associated with a higher risk of LAM defect and loss of anterior vaginal wall support.